Species-level taxonomic characterization of gut microbiota in HIV-infected individuals - Chen, Jiali; Yuan, Tingting; Zheng, Han; Li, Lianfeng; Pu, Ji; Lu, Shan; Sun, Yamin; Lin, Wenchao; Chen, Jun; Guo, Mingquan; Lu, Yubin; Zhu, Zhaoqin; et al. (Frontiers in Microbiology, 2025)
Most current HIV gut microbiota studies, based on 16S rRNA gene sequencing, are limited to the genus level. Since different genera encompass several to hundreds of species, in this study, we performed research at the species level based on the HGMAD database. This cross-sectional study investigated differences in gut microbiota between healthy control (HC) subjects and people with HIV (PWH) at the species level, characterized the specific enterotype and the correlation between gut microbiota patterns and immune status in PWH. We recruited 114 individuals in the PWH group and 58 individuals in the HC group, from whom fecal samples were collected for 16S rRNA gene sequencing of the V3–V4 region. Significant differences in α diversity and β diversity (p-values < 0.05) were observed between the two groups. Compared to the HC group, the PWH group exhibited increased opportunistic pathogens and decreased commensal bacteria. Additionally, 114 species or higher taxa were enriched, while 49 species or higher taxa were depleted in the PWH group relative to those in the HC group. The gut microbiota of the HC group was categorized into enterotype Bacteroides (ET-B) and enterotype Prevotella (ET-P), whereas that of the PWH group exhibited ET-B, ET-P and enterotype Enterobacter (ET-E). ET-E was a unique enterotype in the PWH group, in which the abundance of Enterobacter was significantly increased. The absolute number of CD4+T lymphocytes and CD4/CD8 ratio were lower in ET-E HIV-infected individuals compared to those in the other two enterotypes. Ten signatures in three enterotypes showed high accuracy for distinguishing high and low CD4+T-cell counts groups, as well as high and low CD4/CD8 ratio groups, and the areas under curves were 0.831 (95%CI: 0.734–0.928) and 0.815 (95%CI: 0.721–0.909). Spearman’s correlation analysis revealed that five signatures enriched in the ET-E group were positively correlated with the absolute number of CD8+T lymphocytes. To sum up, compared to the HC group, the gut microbiota of PWH group exhibit reduced microbial diversity, an overall distinct microbial structure, and increased opportunistic pathogens. Furthermore, a novel enterotype (ET-E) was identified in HIV patients. Signatures based on different enterotypes can accurately and effectively discern the immune status of PWH, suggesting that the microbial composition of HIV infection is associated with the immune status.